Study of mechanical behavior of grout sleeve splicing of rebars - Sun, Yuzhe (Frontiers in Physics, 2024)
In order to analyze the influence of grout strength, rebar diameter, sleeve material and anchorage length on performance of grout sleeve splicing of rebars, 72 specimens were designed and fabricated. The experimental results revealed that the failure modes included three forms, namely rebar fracture, sleeve rupture and bond slip between the rebar and grout. The tensile strength increased with the increase of grout strength and anchorage length of rebar at the same time, demonstrating that the sleeve could effectively transfer the bond stress. The sleeve strain gradually increased from the mechanical connection end to the grout connection end, illustrating linear pattern. Based on the failure mechanism of the grout sleeve splicing of rebars and the experimental results, the calculation formula of the anchorage length of grout sleeve splicing of rebars was proposed considering the grout strength and sleeve inner diameter.